Development of a Sway-Based Electronic Module Using a STEM Approach to Enhance Students’ Scientific Literacy - Eka Nurrohmah Khumairoh; Ellianawati, Ellianawati; Lisdiana, Lisdiana (Unnes Science Education Journal, 2025)
Scientific literacy is one of the abilities that encourages students to solve problems. Students still struggle to apply concepts to solve problems in everyday life, presenting a challenge for schools to develop teaching materials that train students’ scientific literacy skills in analyzing and solving problems related to Science, Technology, Engineering, and Mathematics. This study aims to analyze the characteristics, validity, practicality, and effectiveness of the Sway e-module STEM Approach in improving students’ scientific literacy skills. E-modules on the human respiratory system material were developed using the ADDIE development model, with 113 students as research subjects. The results of the study showed that (1) The validity of the Sway e-module STEM approach has a very valid category based on the assessment of five raters. (2) Sway e-module STEM Approach have the ideal characteristics that an e-module with a very good category should have. (3) STEM-based Sway e-modules are very practical to use in the learning process. (4) Sway e-module STEM Approach are effective in improving students’ scientific literacy skills, with an average n-gain of the experimental class of 0.50 and the control class of 0.29. Based on the research results, it can be concluded that e-modules that integrate the STEM approach and are presented using Microsoft Office Sway are more effective in improving students’ scientific literacy skills, especially in the aspect of evaluating and designing scientific questions with indicators of proposing ways to explore scientifically the questions given, with an n-gain of 0.79.